Penerapan Metode Error Level Analysis dan Laplacian of Gausian Untuk Deteksi Tepi Citra CT Scan Paru-Paru - Eferoni Ndruru; Murdani Murdani (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
Edge detection of an image is one way to determine the authenticity of the data, at this time many scans are inefficient due to poor quality and unclear image colors. One of the problems that is often found is in the ct scan results to find out the truth of a disease. In this study, the problems that will be detected are the CT scan results of the lungs using the Error Level Analysis and Laplacian of Gausian method. The identification system can be seen from the results of a good file extraction. Extraction can be done by taking one part of the CT image. scan, and the part that is easiest to find is the edge of the image. The process of applying the Error Level Analysis and Laplacian of gausian method is by combining the Error Level Analysis method and the Lapciaan of gausian method. Method (ELA) a method is a modified image detection technique by restoring a new image, in the sense that it has been compressed after performing the calculation process on changing the compression level of the image. Meanwhile, the Laplacian of gausian method is a technique for detecting the edges of an image, so that the problem solving process is carried out by detecting the modified image and then proceeding to detect the edges of the image to determine the authenticity of the image. The results obtained from this study are the edge detection process of CT-Scan results obtained from the mean value of the Mean Square Error pixel